Tubulin post-translational modifications: the elusive roles of acetylation - Carmona, Bruno (2023)
Microtubules (MTs), dynamic polymers of α/β-tubulin heterodimers found in all eukaryotes, are involved in cytoplasm spatial organization, intracellular transport, cell polarity, migration, division, and cilia biology. MTs functional diversity depends on the differential expression of distinct tubulin isotypes and is amplified by a vast number of different post-translational modifications (PTMs). The addition/removal of PTMs to α- or β-tubulins is catalyzed by specific enzymes and allows combinatory patterns largely enriching the distinct biochemical and biophysical properties of MTs, creating a code read by distinct proteins, including microtubule-associated proteins (MAPs), which allow cellular responses. This review is focused on tubulin-acetylation, whose cellular roles continue to generate debate. We travel through the experimental data pointing to α-tubulin Lys40 acetylation role as being an MT stabilizer and a typical PTM of long-lived MTs, to the most recent data, suggesting that Lys40 acetylation enhances MT flexibility and alters the mechanical properties of MTs, preventing MTs from mechanical aging characterized by structural damage. Additionally, we discuss the regulation of tubulin acetyltransferases/desacetylases and their impacts on cell physiology. Finally, we analyze how changes in MT acetylation levels have been found to be a general response to stress and how they are associated with several human pathologies.